Farmers’ Local Wisdom In Food Security In Danalampah Village, Kuningan Regency, West Java: (A Socio-Cultural Study) - Muhammad Dimas Nugraha; Farida Nurfalah; Leni Rohida (Jurnal Polisci, 2026)
Background. Research on local wisdom in the agricultural sector shows that cultural values play an important role in maintaining agricultural sustainability and food security. Farmers’ local wisdom remains a guiding principle in agricultural practices despite social changes and advances in agricultural technology. Aims. This study aims to identify the forms of local wisdom practiced by farmers in Danalampah Village related to food security, to describe the socio-cultural communication patterns that support its sustainability, and to explain the roles and challenges of local wisdom in the context of agricultural modernization. Methods. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation. The research informants consisted of farmers, farmer groups, and village officials, all purposively selected. Data analysis was conducted through data reduction, data display, and conclusion drawing and verification. Result. The results show that local wisdom is reflected in social values such as cooperation, deliberation, and social solidarity, as well as socio-cultural practices such as botram and Pranata Mangsa (Seasonal Regulations). These values are maintained through interpersonal and group communication patterns that are dialogic and communal. Conclusion. Local wisdom plays an important role in maintaining agricultural production stability, agricultural sustainability, and social cohesion within the community. Implementation. Agricultural modernization presents various challenges; the community adapts by combining local knowledge with modern information so that community-based food security remains sustainable.